Diper Overlode - Kinney, Jeff (UK, 2022)
Greg Heffley is finding out that the road to fame and glory comes with some hard knocks. When he decides to tag along with his teenage brother Rodrick's band, Loded Diper, Greg doesn't realize what he's getting into. But he soon learns that late nights, unpaid gigs, fights between band members and money troubles are all part of the rock 'n' roll lifestyle. Can Greg help Loded Diper become the legends they think they are? Or will too much time with Rodrick's band be a Diper Overlode?...
Keywords: Adventure; Family / Siblings; Juvenile Fiction